Is graduated pressure profile an essential feature for compression stockings to reduce fatigue development of the plantar flexors? - Miyamoto, N. (Sports Performance, 2015)
Most sports compression stockings have employed a graduated pressure profile. This pressure profile is based on positive evidence from the medical literature on patients. However, no consensus has been reached as to whether or not the graduated pressure profile is an essential feature for reducing muscle fatigue development in the lower legs. The purpose of the present chapter is to examine the pressure profile of compression stockings on the degree to which muscle fatigue of the plantar flexors develops during repetitive calf-raise exercise. Thirteen male subjects completed 12 sets of 10 repetitions of calf-raise exercise in one control (barefoot) and three compression stocking conditions with the following pressure profiles; (1) graduated pressure profile (GRA), (2) uniform pressure distribution (UNI), and (3) localized pressure at the calf region just over the gastrocnemius muscle belly (LOC). During the exercise, ankle joint angle and electromyographic signals from the medial gastrocnemius and soleus were recorded. The plantar flexion angle significantly decreased with repetitions of the calf-raise under all conditions. The plantar flexion angles were significantly smaller in CON than in the GRA, UNI and LOC conditions, whereas there was no significant differences among GRA, UNI and LOC conditions. No significant difference was observed in muscle activities of the medial gastrocnemius and soleus during the exercise among the four conditions. These findings suggest that peripheral muscle fatigue of the plantar flexors was relieved when wearing the compression stockings used in the present study. In addition, the results indicate that a graduated pressure profile is not an essential feature for compression stockings to reduce development of muscle fatigue during repetitive plantar flexion exercise.